Perbandingan Efektivitas Media Edukasi Mitigasi Bencana pada Anak Sekolah Dasar: Video Edukasi, E-Komik, Buku Cerita, dan Virtual Reality - Rifandi, Raditya Ahmad; Syah Putra, Rizal Ichsan (Environmental Science Program, Ivet University, 2024)
This study compares the effectiveness of four disaster mitigation education media—educational videos, e-comics, storybooks, and Virtual Reality (VR)—in improving elementary school students’ understanding, engagement, and motivation in disaster-prone areas, particularly in Central Java. Using a quantitative questionnaire-based survey method on 143 students and 16 teachers, the results showed that e-comics were the most effective media. E-comics significantly improved students’ understanding of disaster mitigation concepts (average score of 4.5), attracted students’ engagement (average score of 4.7), and motivated them to act in disaster situations (average score of 4.6). These advantages were driven by interactive visual elements and relevant stories that made it easier for students to understand the material. In contrast, media such as VR and storybooks have limitations related to accessibility and interactive nature. This study recommends the use of e-comics as the main educational media in disaster mitigation learning at the elementary school level.